Criminological research for beginners a student's guide - Caulfield, Laura 1981-; Hill, Jane 1954- (Routledge, 2014)
[This book] is a comprehensive and engaging guide to research methods in Criminology. Written specifically for undergraduate students and novice researchers, this book has been designed as a practical guide to planning, conducting, and reporting research in the subject. By first inviting readers to consider the importance of criminological research, the book places related methodology firmly in the context of students' broader study of Criminology, before moving on to provide a detailed guide to the practical processes of research. It is common for Criminology undergraduates to feel intimidated at the prospect of conducting their own research, and these students typically struggle to see the relevance of research methods to their own studies. This book speaks directly to the needs of such students, and includes contemporary examples and case studies that bring a topic that is often thought of as dry to life, providing a thorough and accessible practical guide that students can return to at each stage of their research, all the way through to their dissertation.